Cyber-Bystander Behavior Among Canadian and Iranian Youth: The Influence of Bystander Type and Relationship to the Perpetrator on Moral Responsibility - Nagar, Pooja Megha; Leduc, Karissa; Khalili, Nadia; Talwar, Victoria (Frontiers in Communication, 2022)
The current study examines how social determinants influence the way youth from Canadian and Iranian contexts evaluate and morally disengage as bystanders of cyberbullying. While Iranian culture differs from other individualistic and collectivist cultures, Iranian youth have become just as technologically acculturated as their global peers. Despite this, less is understood about how Iranian youth respond to cyberbullying in comparison to youth from individualistic societies. Participants from Canada (N = 60) and Iran (N = 59) who were between the ages of 8-to-15 years old (N = 119, M = 11.33 years, SD = 1.63 years) read 6 cyberbullying scenarios that varied according to Bystander Relationship to Perpetrator (Acquaintance or Friend) and Bystander Response (Assists Cyberbully, Does Nothing, Defends Victim). After reading each scenario, participants were asked to evaluate the bystander’s behavior. They were also asked how they would feel if they were the bystander. Similar to past research (Conway et al., 2016), these responses were coded on a continuous scale ranging from morally disengaged to morally responsible. Overall, Canadians were more critical of passive bystander behaviors and more supportive towards defending behaviors compared to Iranians. Iranians were more supportive of the behaviors of bystanders who were friends of perpetrators than Canadians were, and Iranians were more critical towards acquaintances of perpetrators. Significant interactions were also found between participants’ country of origin, the bystander’s relationship with the perpetrator and the bystander’s behavior. Taken together, these findings highlight the importance of differentiating between negative judgments and moral attributions of bystander responses.